Growth and Quality of Acacia nilotica Seedlings Raised in Root Trainers with Potting Media Varying in Physical and Chemical Properties in Arid Zone - Prasad, Rajendra; Lohra, R R; Mertia, R S; Rathore, S S; Shukla, Upendra; Kumar, Sushil (Annals of Arid Zone, 2016)
A nursery experiment was conducted to assess the effect of eight different potting media varying in physical and chemical properties, on growth and quality of A. nilotica seedlings raised in root trainer containers. Data relating to plant height, collar diameter, root CEC, root nodulation and production of biomass have been discussed. Seedling quality parameters like sturdiness, root shoot ratio, Dickson Quality Index and comparison index were calculated. Based on seedling growth and quality parameters, the medium comprising of soil:compost’ (20:80) was found most superior followed by medium comprising of compost:rice husk:pearl millet husk ( O:20:20). The correlation matrix between seedling parameters and properties of treatment mixture revealed that many seedling growth and quality traits are influenced significantly by the physical and chemical properties of the potting mixtures. Results of the study indicate that one has to be careful in choosing right combination of different ingredients so that the physical and chemical properties of the medium remain desirable and favorable for the growth of seedlings.